An Investigation on the Fatigue based Delamination of Woven Carbon-epoxy Composite Laminates Reinforced with Polyamide Nanofibers. (2015) - Brugo, T.M.; Minak, G.; Zucchelli, A.; Saghafi, H.; Fotouhi, M.
Abstract: Delamination is the most frequent failure mode in laminated composite materials and it may cause catastrophic failure in critical engineering structures. One of the ways to prevent this failure is to toughen the crack against initiation and propagation. There is lack of studies in literature for toughening the delamination using nanofibers, especially in the case of fatigue behavior. Therefore, the present work aims to investigate effect of interleaved nanofiber mat on fatigue interlaminar properties of mode I delamination in carbon-epoxy composite laminates. To reach this aim, the electrospun polyamide nanofiber fabrics were put in the mid-plane of woven carbon/epoxy laminates. Then the fatigue Double Cantilever Beam (DCB) tests were performed on both virgin and nanomodified specimens, based on ASTM D6115. The experimental results show that the interlaminar fracture toughness and delamination onset fatigue life of the specimens can be substantially improved by addition of the Polyamide nanofiber interlayer. As a matter of fact, there is negligible increase in the thickness of the specimens, less than 1%, but there is noticeable out-plane mechanical properties increase of the modified specimens. The increases in the delamination toughness are up to 150%, at the static tests, and around 100% at the high cycle fatigue loading conditions. Crack paths were investigated by micrograph analysis and different behaviors in the virgin and nano-modified ones were observed and related to the different mechanical results.